2020
DOI: 10.1177/0361198120946016
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Average Annual Daily Bicycle Counts using Crowdsourced Strava Data

Abstract: Traffic volumes are fundamental for evaluating transportation systems, regardless of travel mode. A lack of counts for non-motorized modes poses a challenge for practitioners developing and managing multimodal transportation facilities, whether they want to evaluate transportation safety or the potential need for infrastructure changes, or to answer other questions about how and where people bicycle and walk. In recent years, researchers and practitioners alike have been using crowdsourced data to supplement t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…A study in Miami found that Strava sampling rates were higher on streets than trails (26), while another found areas with more bike lanes to have lower sampling rates (25). However, these third-party data sources, of which most have focused on Strava thus far, have usually improved bicycle volume and safety performance models significantly, after controlling for built environment and sociodemographic factors (1,(28)(29)(30)(31)(32)(33)(34). Despite consistent findings of association, a few details are worth noting: Correlation does not necessarily track sampling ratio.…”
Section: Data Sources For Bicycle Volumesmentioning
confidence: 99%
“…A study in Miami found that Strava sampling rates were higher on streets than trails (26), while another found areas with more bike lanes to have lower sampling rates (25). However, these third-party data sources, of which most have focused on Strava thus far, have usually improved bicycle volume and safety performance models significantly, after controlling for built environment and sociodemographic factors (1,(28)(29)(30)(31)(32)(33)(34). Despite consistent findings of association, a few details are worth noting: Correlation does not necessarily track sampling ratio.…”
Section: Data Sources For Bicycle Volumesmentioning
confidence: 99%
“…The XGBoost comes in two versions: the Linear Booster and Tree Booster (Chen and Guestrin, 2016). It is noteworthy that these machine learning algorithms have been used in many application fields in the literature including cycling and transportation (Dadashova et al, 2020; Khasawneh et al, 2020; Litzenberger et al, 2018; Mahmoud et al, 2021; Munira and Sener, 2020; Sun and Mobasheri, 2017). To compare their performance, we tuned each model parameter separately to minimize the mean absolute error (MAE) and to maximize R 2 .…”
Section: Machine Learning Analysismentioning
confidence: 99%
“…The data represent up to five percent of total cycling volume and tend to overrepresent white, middle-aged men (Lee and Sener, 2020;Nelson et al, 2020). Research has shown that, with adjustment, Strava Metro data can predict cycling volumes with under 30 percent measurement error (Dadashova et al, 2020). But others have shown that the data by themselves serve as reasonable proxies for cycling exposure (Lee and Sener, 2020), and so I use the Strava data here without adjustment.…”
Section: Datamentioning
confidence: 99%